Analisis Laporan dan Buku Besar Pada E-commerce Dalam Penerapan Aplikasi Konsep Database Relasional : Studi Kasus Pada Aplikasi Shopee - Pinasthika Alya Disti; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to analyze the reports and ledgers on the Shopee e-commerce platform by applying the concept of a relational database. The main focus of this study is how the Shopee application manages user transaction data and compiles accurate and structured financial reports. The methodology used in this research includes data collection through documentation and system observation as well as interviews with relevant parties. The collected data were analyzed using a descriptive and quantitative approach to identify patterns and relationships among the data in the relational database system.The results of the study indicate that the application of the relational database concept in the Shopee application allows for more efficient and consistent data management. By using interconnected tables, the application can present detailed and accurate transaction information in the form of daily, monthly, and yearly reports. Additionally, the use of primary and foreign keys in the tables helps ensure data integrity and prevent redundancy. The ledgers generated from this system also show clear correlations between various accounts and transactions, facilitating the audit and financial examination process.Overall, this study underscores the importance of applying the relational database concept in e-commerce systems to improve data management accuracy and efficiency. These findings are expected to serve as a reference for other e-commerce application developers in optimizing their database systems